Frequency of Trichomonas vaginalis, Candida sp and Gardnerella vaginalis in cervical-vaginal smears in four different decades - Adad, Sheila Jorge (2001)
CONTEXT: Vaginitis is one of the principal motives that lead women to seek out an obstetrician or gynecologist. Bacterial vaginosis, candidiasis and trichomoniasis are responsible for 90% of the cases of infectious vaginitis. OBJECTIVE: To verify the frequency of the three main causative agents of vaginitis,Trichomonas vaginalis, Candidasp and Gardnerella vaginalis,in four different decades (1960’s, 1970’s, 1980’s and 1990’s). DESIGN: Retrospective. PLACE: A tertiary referral center. PARTICIPANTS: Patients attended to as gynecology and obstetricsoutpatientsatthe Faculdadede Medicina doTriângulo Mineiro during the years1968,1978, 1988, 1998, taken as samples of each decade. MAIN MEASUREMENTS: Diagnoses of infection by Trichomonas vaginalis,Candida sp and Gardnerella vaginalis were ga thered from 20,356 cervical-vaginal cytology tests on patients attended to as gynecology outpatients at Faculdade de Medicina doTriângulo Mineiro during the years1968,1978,1988,1998, representing the four decades. The results were grouped according to the age group of the patients: under 20, between 20 and 29, between 30 and 39, between 40 and 49, and 50 or over. Statistical analysis was done via the chi-squared (Mantel- Haentzel) test with a significance level of 5%. RESULTS: In 1968 infections by Trichomonas vaginalis and Candida sp were diagnosed in 10% and 0.5% of the cytology tests and in 1978,5.1%and17.3%, respectively (P < 0.0001). Infection by Gardnerella vaginalis could only be evaluated in the latter two decades.In1988,19.8%of the women had positive tests for Gardnerella vaginalis, which was the most frequent agent in that year, diminishing in the subsequent decade to 15.9% (P < 0.0001). Candidiasis was the most frequent infectionin1998, detected in 22.5% of the tests (P < 0.0001). In a general manner,all the infections were most frequent among younger patients, especially those age dunder 20, in all decades, whereas infections were least frequent among patients aged 50 or over(P<0.05). CONCLUSION: There was a reduction in the frequency of cervical-vaginal infection by Trichomonas vaginalis and an increase in the frequency of Candidas pover the four decades studied. All the infections were most frequentin patients age dunder 20 years.